SpyCEP dismantles neutrophil immunity via disorder-driven chemokine remodeling and GAG targeting - Rikin J. Lau; Sean P. Giblin; Andra Sugar; Antonio Di Maio; Giulio Tassini; Kristin Huse; Dror Chorev; Yuan Chen; Grace Ho-Yan Wu; Camilla Berg Huemer; Seung Yon Kim; Jayden Matthews; et al. (Proceedings of the National Academy of Sciences, 2026)
Streptococcus pyogenes (Group A Streptococcus ) employs sophisticated virulence strategies to evade human immunity, including secretion of the cell envelope protease SpyCEP, which cleaves and inactivates key neutrophil-attracting chemokines such as CXCL8. Here, we integrate cryo-electron microscopy, NMR spectroscopy, and native mass spectrometry to investigate how SpyCEP disrupts CXCL8 function. We demonstrate that a disordered aromatic and acidic region within the cleaved autocatalytic maturation loop (CAML) of SpyCEP mimics receptor N-domains and binds an allosteric site on CXCL8. The resulting interaction forms a dynamic fuzzy complex and is coupled to dimer dissociation, consistent with enhanced access to the cleavage site. This disorder-mediated substrate engagement differs from classical protease mechanisms that rely on rigid recognition interfaces. Additionally, glycan microarray and NMR analyses show that the CAML region mediates glycosaminoglycan (GAG) binding, suggesting a means for SpyCEP to maximize encounters with GAG-enriched CXCL8 reservoirs. Together, these findings provide a structural and biophysical framework for understanding how SpyCEP combines substrate engagement with GAG targeting to dismantle chemokine gradients and inhibit neutrophil recruitment. More broadly, this work highlights the role of intrinsic disorder in protease recognition and suggests avenues for anti-virulence therapies and vaccine strategies targeting SpyCEP.